Syarie Lawyer in Pahang; Its Challanges, Problems and Remedies - Muhamad Safri B. Hj. Ibrahim (2022)
Syarie Lawyer in Pahang; Its Challenges, Problems and Remedies is a title of this academic project. There are two types of method used in this project paper. There are field research and library research. There are many interesting topics and issues, which had been discussed by the author in his academic project, such as the background of the Syarie Lawyer existence in the world. It is also focused in qualifications to become a Syarie Lawyer in Malaysia and in Pahang specifically. The author also discussed about the functions and responsibilities of Syarie Lawyer. Besides, there are several problems and challenges faced by the Syarie Lawyer in Pahang nowadays and author had found a few solutions and remedies in this project paper. It is taken from variety of ideas, views and opinions of the great academicians in Malaysia who have specialized in their own field.